Plant immunity: Good fences make good neighbors?. (August 2021) - Pélissier, Rémi; Violle, Cyrille; Morel, Jean-Benoit
Abstract: Plant immunity is modulated by several abiotic factors, and microbiome has emerged as a major biotic driver of plant resistance. Recently, a few studies showed that plants also modify resistance to pests and pathogens in their neighborhood. Several types of neighborhood could be identified depending on the biological processes at play: intraspecific and interspecific competition, kin and stranger recognition, plant-soil feedbacks, and danger signaling. This review highlights that molecules exchanged aboveground and belowground between plants can modulate plant immunity, either constitutively or after damage or attack. An intriguing relationship between allelopathy and immunity has been evidenced and should merit further investigation. Interestingly, most reported cases of modulation of immunity by the neighbors are positive, opening new perspectives for the understanding of natural plant communities as well as for the design of more diverse cultivated systems. Highlights: Plants share signals and cues that affect their immune system. This modulation of immunity affects their resistance to insects and pathogens. Recent discoveries support the idea that immunity is also generated through allelopathic response to strangers. The modulation of immunity by plant–plant interactions may have strong ecological consequences.